Hubungan Perilaku Picky Eater dengan Status Gizi pada Anak Usia Dini : The Relationship between Picky Eater Behavior and Nutritional Status in Early Childhood - Sa'adah, Firdaus (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
A common eating problem in early childhood is picky eater behavior, where children are picky about food and refuse to eat or try new foods. Parenting patterns, parental eating behavior, mother-child interactions, exclusive breastfeeding or MPASI, psychological and physical conditions of children are influenced by picky eater behavior, which can cause micro and macro nutrient deficiencies. This study is important to study because there are problems with food consumption patterns in early childhood that can affect child growth and development. This type of research uses the SLR (Literature Review Study) method. The purpose of the literature review is to develop basic concepts and research frameworks regarding the problem of picky eater behavior. Research articles must meet the following criteria: a) research subjects are early childhood; b) picky eater behavior in early childhood institutions in Indonesia; and c) nutritional status in early childhood. This article found that early childhood in early childhood institutions experience picky eater behavior which results in low nutritional value of food consumed by children. As a result, the child's nutritional status is low and falls into the category of malnutrition. Picky eaters often appear in toddlers and have a two-fold greater risk of being underweight compared to children who are not picky eaters.   ABSTRAK Masalah makan yang umum terjadi pada anak usia dini adalah perilaku picky eater, di mana anak memilih-milih makanan dan menolak untuk makan atau mencoba makanan baru. Pola asuh, perilaku makan orang tua, interaksi ibu dan anak, pemberian ASI eksklusif atau MPASI, kondisi psikologis dan fisik anak dipengaruhi oleh perilaku picky eater, yang dapat menyebabkan kekurangan zat gizi mikro dan makro. Penelitian ini penting untuk diteliti karena terdapat masalah pola konsumsi makanan pada anak usia dini yang dapat mempengaruhi tumbuh kembang anak. Jenis penelitian ini menggunakan metode SLR (Studi Kajian Literatur). Tujuan dari tinjauan pustaka adalah untuk menyusun konsep dasar dan kerangka pemikiran penelitian mengenai permasalahan perilaku picky eater. Artikel penelitian harus memenuhi kriteria sebagai berikut: a) subjek penelitian adalah anak usia dini; b) perilaku picky eater di lembaga PAUD di Indonesia; dan c) status gizi pada anak usia dini. Artikel ini menemukan bahwa anak usia dini di lembaga PAUD mengalami perilaku picky eater yang berujung pada rendahnya nilai gizi makanan yang dikonsumsi anak. Akibatnya, status gizi anak menjadi rendah dan masuk dalam kategori gizi kurang. Picky eater sering muncul pada usia balita dan memiliki risiko dua kali lipat lebih besar untuk mengalami berat badan kurang dibandingkan dengan anak yang tidak picky eater.